Neuropsychological effects of brain autograft of adrenal medullary tissue for the treatment of Parkinson's disease - Ostrosky-Solís, F; Quintanar, L; Madrazo, I; Drucker-Colín, R; Franco-Bourland, R; Leon-Meza, V (Neurology, 1988)
We describe the pre- and postoperative neuropsychological profiles of seven patients who received an autograft of adrenal medullary tissue to the caudate nucleus for the treatment of Parkinson's Disease (PD). The preoperative neuropsychological evaluations revealed specific cognitive deficits of varying degree. The patients showed frontal lobe-type deficits with alterations in behavioral programming leading to difficulties in the organization of motor sequences and alternating programs. They also showed memory disorders and visuospatial and visuoperceptual deficiences such as a loss of figure-ground perspective and fragmentation. Postoperative evaluations, carried out 3 months after neurosurgery, revealed a significant amelioration of the frontal lobe-type symptoms and visuospatial deficits, as well as an improvement in memory tasks that require an active organization of the response. Immediate and delayed memory difficulties remained unchanged. These observations were compared to neuropsychological data obtained from neurologically intact subjects and from unoperated PD patients. The improvements of the operated PD patients resulted in performance levels close to normal values and clearly distinguishable from those of unoperated PD patients, and were unrelated to improved mood, increased alertness, or sustained attention. Autotransplantation of adrenal medullary tissue to the caudate nucleus of PD patients showing a decreased effective response to L-dopa therapy can partially restore motor functions and frontal-type cognitive symptoms.